Constraints of hierarchy on meso-actors' agency: evidence from Vietnam's educational language policy reform. Issue 1 (15th March 2021) - Shepherd, Elizabeth; McEntee-Atalianis, Lisa
ABSTRACT: This paper contributes to recent discussions of levels of agency in Language Policy and Planning (LPP) research. It specifically aims to understand the role and importance of meso-level actors as arbiters of policy implementation. It argues that, whilst understanding of both macro- and micro-agency has grown over the past decade, little is understood about the experience of meso-level agents. The paper seeks to address this by focussing on the LPP context in Vietnam; in particular, the implementation of the 2008 National Foreign Languages Project 2020. It explores the undertheorised and yet important socio-cultural context in which educational LPP takes place. Contrary to previous research which found that language policy arbiters can, in some cases, possess a disproportionate amount of power, this paper shows how Governments and institutions can act to limit rather than empower meso-level agents. The thematic analysis focuses on how meso-level agents perceive their role and the extent to which the setting in which they work impacts on their capacity to act. The paper argues that lack of information and support for meso-level agents participating in language policy implementation significantly constrains their ability to facilitate policy change.